Fluoxetine-induced androgenic failure impairs the seminiferous tubules integrity and increases ubiquitin carboxyl-terminal hydrolase L1 (UCHL1): Possible androgenic control of UCHL1 in germ cell death? - Camara, Marina L. [UNESP]; Almeida, Talita B. [UNESP]; Santi, Fabiane de; Rodrigues, Beatriz M. [UNESP]; Cerri, Paulo S. [UNESP]; Beltrame, Flavia L.; Sasso-Cerri, Estela [UNESP] (Elsevier B.V., 2019)
The selective serotonin reuptake inhibitor fluoxetine has been used for the treatment of depression. Although sexual disorders have been reported in male patients, few studies have demonstrated the fluoxetine effect on the reproductive histophysiology, and the target of this antidepressant in testes is unknown. We evaluated the impact of short-term treatment with fluoxetine on the adult rat testes, focusing on steroidogenesis by Leydig cells (LC) and androgen-dependent testicular parameters, including Sertoli cells (SC) and peritubular myoid cells (PMC). Since UCHL1 (ubiquitincarboxyl-terminal hydrolase L1) seems to control spermatogenesis, the immunoexpression of this hydrolase was also analyzed. Adult male rats received 20 mg/kg BW of fluoxetine (FG) or saline (CG) for eleven days. In historesin-embedded testis sections, the seminiferous tubule (ST) and epithelial (Ep) areas, and the LC nuclear diameter (LCnu) were measured. The number of abnormal ST, androgen-dependent ST, SC and PMC was quantified. Testicular beta-tubulin levels and peritubular actin immunofluorescence were evaluated. Serum testosterone levels (STL) and steroidogenesis by 17 beta-HSD6 immunofluorescence were analyzed, and either UCHL1-immunolabeled or TUNEL-positive germ cells were quantified. In FG, abnormal ST frequency increased whereas ST and Ep areas, androgen-dependent ST number, LCnu, 17 beta-HSD6 activity and STL reduced significantly. TUNEL-positive PMC and SC was related to decreased number of these cells and reduction in peritubular actin and beta-tubulin levels. In FG, uncommon UCHL1-immunoexpression was found in spermatocytes and spermatids, and the number of UCHL1-immunolabeled and TUNEL-positive germ cells increased in this group. These findings indicate that LC may be a fluoxetine target in testes, impairing PMC-SC integrity and disturbing spermatogenesis. The increase of UCHL1 in the damaged tubules associated with high incidence of cell death confirms that this hydrolase regulates germ cell death and may be controlled by androgens. The fertility in association with the androgenic status of patients treated with fluoxetine should be carefully evaluated.
Keywords: SSRI; Spermatogenesis; Peritubular myoid cell; Sertoli cell; Steroidogenesis; Ubiquitin hydrolase